2022
DOI: 10.1089/end.2021.0075
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Preoperative Predictors of Operative Time and Their Impact on Outcomes in Robot-Assisted Partial Nephrectomy

Abstract: Objective: To identify preoperative characteristics in patients with renal masses that influence operative time during robot-assisted partial nephrectomy (RAPN) and evaluate the relationship between operative time and length of stay, complication rates, and overall outcome. Methods:We queried our institutional database to identify a cohort of patients who underwent RAPN by two experienced robotic surgeons between 2012 and 2019. A multivariable regression model was developed to analyze operative time, length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…Our findings add to a collection of recent studies on RAPN that have shown increased operative time for high complexity cases, as indicated by an increasing nephrometry score [ 14 ]. Okhawere et al reported shorter operative times in an SP cohort compared to an MP cohort for high complexity (nephrometry score = 10–12) renal masses, as well as shorter operative times in a high complexity SP group compared to low and intermediate complexity SP groups [ 15 ].…”
Section: Discussionsupporting
confidence: 73%
“…Our findings add to a collection of recent studies on RAPN that have shown increased operative time for high complexity cases, as indicated by an increasing nephrometry score [ 14 ]. Okhawere et al reported shorter operative times in an SP cohort compared to an MP cohort for high complexity (nephrometry score = 10–12) renal masses, as well as shorter operative times in a high complexity SP group compared to low and intermediate complexity SP groups [ 15 ].…”
Section: Discussionsupporting
confidence: 73%
“…Our ndings add to a collection of recent studies on RAPN that have shown increased operative time for high complexity cases, as indicated by an increasing nephrometry score [14]. Okhawere et al reported shorter operative times in an SP cohort compared to an MP cohort for high complexity (nephrometry score = 10-12) renal masses, as well as shorter operative times in a high complexity SP group compared to low and intermediate complexity SP groups [15].…”
Section: Discussionsupporting
confidence: 64%
“…OT is a critical factor, as it not only affects patient outcomes but also has implications for resource utilization and the efficiency of surgery. While concerns exist regarding the potential drawbacks of increased operative duration, such as increased anesthesia exposure and longer LOS [10], extended OT did not lead to a higher rate of perioperative complications according to our results. Similar data have been reported in studies assessing the impact of the level of assistant experience on other urological minimally invasive surgical procedures.…”
Section: Discussionsupporting
confidence: 43%
“…The potential risks associated with having less experienced assistants in the operating room, such as longer operative times [7,8], negative impacts on patient outcomes [9][10][11], and increased risk of surgical complications [11], highlight the importance of understanding the dynamics of resident involvement in laparoscopic nephrectomy. Evidence of the actual impact of resident expertise on surgical outcomes of laparoscopic radical or simple nephrectomy is lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%